Lignan 7-hydroxymatairesinol in the context of post-genomic pharmacology - А. N. Rubashkina; I. Yu. Torshin; O. A. Gromova; A. N. Galustyan (Фармакоэкономика)
Objective: to determine the molecular mechanisms of action of 7-hydroxymatairesinol (7(OH)MR), the main lignan of spruce extracts, characterized by oncoprotective and anti-inflammatory properties.Material and methods. The analysis of 7(OH)MR was carried out by chemoinformatic approach using the combinatorial theory of solvability and the topological theory of recognition. The postgenomic approach makes it possible to assess the effect of drugs on genome transcription (transcriptome) and on the proteome as a whole.Results. 7(OH)MP has anti-inflammatory (inhibition of 5-lipoxygenase, matrix metalloproteinase 2, mitogen-activated kinase p38-alpha, leukotriene В4 receptor, prostacyclin receptor), and oncoprotective (antioxidant effect due to inhibition of heme oxygenase-2, inhibition of cyclin-dependent kinases 3 and 4, epidermal growth factor, mTOR protein) pharmacological effects.Conclusion. By reducing the expression of proliferative genes and genes involved in chronic inflammation, the 7(OH)MP molecule inhibits the proliferation of tumor cells. Pharmacoinformatic modeling showed that the anti-inflammatory effects of 7(OH)MR may contribute to increased lifespan in animal models.